(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The paper presents the study of multi-PTO interaction in single-air chamber oscillating-water-column (OWC) wave energy converters (WECs). This strategy seeks: i) tunning system’s performance to sea states, ii) increasing reliability through modular designs that are easier to install and replace, and iii) increasing conversion efficiency through better matching between available power and electric conversion equipment. The strategy was assessed through a novel non-linear time-domain model for OWC WECs implemented in the multi-physics object-oriented language Modelica. The model considers multiple degrees of freedom associated with the various PTOs. Different case studies are presented to show the proposed approach’s versatility, some of the constraints expected in real implementations, and potential pathways to overcome them. The wave-to-wire model considers air compressibility and non-linear power take-off systems, which is fundamental to assessing the damping level variation required for each sea state considered. The cases presented are for a fixed-structure coaxial-duct OWC WEC, but the results are generalisable for floating structures. Results show a significant increase in mean annual power, and control strategies are proposed for power maximisation. Furthermore, some critical points are shown in the operational conditions’ envelop for the system under a selected Portuguese wave climate. The identification of these critical values is important for the control of the OWC WECs. This study represents an advance in the control strategies considering multiple PTOs for a single OWC air chamber to foster innovation actions.